Mineral Resource Modelling and Reconciliation in Ultra Deep Underground Gold Mines - R C. A Minnitt (The Australasian Institute of Mining and Metallurgy, 2011)
The Witwatersrand Supergroup is host to the world’s largest gold deposits. The location, quantity, grade, continuity and other geological characteristics of a Mineral Resource are either known, estimated from specific geological evidence and knowledge, or interpreted from a well constrained and portrayed geological model. Establishing such a model is an integral part of the evaluation process in the Anglogold Ashanti (AGA) group, and is referred to as a Geoscience Business Model for the mining operations. The geological model established over the years has relied on detailed descriptions of the mineralisation, and understanding of the regional and local geology of the Witwatersrand sediments, in the West Wits and Free State goldfields. The processes of data collection in regard to underground stope and developing mapping, structural and sedimentological mapping, and the geological inputs to mine planning systems are described, together with aspects of drilling, sampling, grade control, and data management. Anglogold Ashanti’s Geoscience Department employs a complex and unique process to generate the Mineral Resource, including a 3D geological structure model of the orebodies which are usually highly faulted, and a robust mineralisation/facies model on which the decisions about domain boundaries are established. A Mineral Resource Inventory System (MRIS) has a dynamic graphic interface to the resource database that is used for compiling the resource statement. It is also used to determine the gold-called-for, as well as short and long-term planning. A unique estimation process using the extensive closely spaced stope face sampling database and the more widely spaced surface drilling information is used in combination in the Macro Co-Kriging estimation. The use of different support sizes in the C0-Kriging process is preceded by the equally unique ‘clusterisation’ and ‘acceptorisation’ procedures by which the data are quality controlled and assured prior to their use in the kriging process. The Mineral Resource and Ore Reserve estimates are classified according to the SAMREC code through a method that ensures that they are compliant, auditable, transparent and reconcilable with previous Mineral Resource and Ore Reserve statements.